ANALISIS KESALAHAN PENGGUNAAN BAHASA INDONESIA PADA AKUN INSTAGRAM @ANWAR_BAB: TINJAUAN LINGUISTIK DI PLATFORM MEDIA SOSIAL - Andriani, Rina; Saputra, Desma Yuliadi; Fauzi, Rizal (Universitas Sultan Ageng Tirtayasa, 2024)
This study examines language errors at the spelling level in Anwar Sanjaya Pigano's Instagram posts. The purpose of this study is to describe the forms of language errors in 13 of Anwar Sanjaya Pigano's Instagram posts, particularly in the area of spelling, which include errors in writing non-standard words and errors in the use of punctuation that do not comply with Ejaan Yang Disempurnakan (EYD V). The research method used is descriptive with qualitative data analysis techniques. The data source used in this study is the captions in Anwar Sanjaya Pigano's Instagram posts. The results show the forms of language errors at the spelling level, both in terms of non-standard word writing and errors in punctuation usage that do not comply with Ejaan Yang Disempurnakan (EYD V). The conclusion of this study is that there are language errors in Anwar Sanjaya Pigano's Instagram posts in 2023, in the form of non-standard word writing and the use of punctuation that does not comply with the Ejaan Yang Disempurnakan (EYD V).